Periventricular White Matter Alterations From Explosive Blast in a Large Animal Model: Mild Traumatic Brain Injury or "Subconcussive" Injury?. Issue 6 (7th April 2020) - Kim, Jung H; Goodrich, James A; Situ, Robert; Rapuano, Amedeo; Hetherington, Hoby; Du, Fu; Parks, Steve; Taylor, Wesley; Westmoreland, Ted; Ling, Geoffrey; Bandak, Faris A; de Lanerolle, Nihal C
Abstract: The neuropathology of mild traumatic brain injury in humans resulting from exposure to explosive blast is poorly understood as this condition is rarely fatal. A large animal model may better reflect the injury patterns in humans. We investigated the effect of explosive blasts on the constrained head minimizing the effects of whole head motion. Anesthetized Yucatan minipigs, with body and head restrained, were placed in a 3-walled test structure and exposed to 1, 2, or 3 explosive blast shock waves of the same intensity. Axonal injury was studied 3 weeks to 8 months postblast using β-amyloid precursor protein immunohistochemistry. Injury was confined to the periventricular white matter as early as 3–5 weeks after exposure to a single blast. The pattern was also present at 8 months postblast. Animals exposed to 2 and 3 blasts had more axonal injury than those exposed to a single blast. Although such increases in axonal injury may relate to the longer postblast survival time, it may also be due to the increased number of blast exposures. It is possible that the injury observed is due to a condition akin to mild traumatic brain injury or subconcussive injury in humans, and that periventricular injury may have neuropsychiatric implications.